Estudo fitoquímico, das atividades biológicas e do efeito anti hiperglicemiante da Sida rhombifolia Linn. (Malvaceae) sobre parâmetros bioquímicos e hematológicos - Teixeira, Marianne Pinheiro (2023)
The species Sida rhombifolia Linn, popularly known as “guanxuma”, has several popular therapeutic uses. Therefore, this study aimed to investigate the ethanolic extract of the species, which was subjected to qualitative and quantitative tests regarding the content of secondary metabolites using spectrometric methods and chromatographic tests to outline its profile. The study also describes the antioxidant potential through DPPH and ABTS tests. and cellular spectrum. Also analyze the hypoglycemic and lipid-lowering activity in Wistar rats. For this evaluation, the extract was administered orally to healthy and diabetic Wistar rats induced by a high-calorie diet and the adjuvant action of streptozotocin. The animals (n=25) were divided into 5 groups and periodically evaluated for blood glucose, water intake, food intake and weight loss. At the end of the study, blood, kidney, heart and spleen were collected to evaluate biochemical parameters (glycemia, liver (AST and ALT), kidney (creatinine) and lipid (total cholesterol) and inflammatory adipokines) and hematological parameters. The content of total polyphenols was 134.0±0.25 mg/g, total flavonoids 14.46±0.05 mg/g and condensed tannins 30.7±0.11 mg/g of VHS. In the HPLC-MS analysis, the compound with the highest concentration was isoquercetrin (3.00±0.077 mg/g), followed by the results of apigenin (2.02±0.01 mg/100g) and results of kaempferol (135. 87 ±0.01mg/g). In the CG-DIC analysis, specific for fatty acids, the highest concentrations were palmitic, linoleic and alpha-linolenic acids, respectively. The DPPH method presented an IC50 value of 1554.92 ± 0.18 µg/mL and ABTS the FRS% value was 101.8. MTT results do not contain cytotoxic effect concentration. The data observed in this research shows therapeutic potential in the species. Sida rhombifolia leaf extract, at doses of 200 and 400 mg/kg/day, showed some positive, but moderate, physiological interferences in some hematological and biochemical parameters characteristic of diabetes. Analysis of the results obtained in this work suggests that new trials with doses higher than those used are necessary to verify the effectiveness of ESR. The groups treated with S. rhombifolia showed higher food consumption and body weight, and lower glycemic indexes, the plant improved the profile of interleukins and inflammatory adipokines.